2007
DOI: 10.1186/1471-2415-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension: the association between weight loss and the requirement for systemic treatment

Abstract: BackgroundTo determine whether weight loss is significantly associated with a discontinuation of treatment for idiopathic intracranial hypertensionMethodsThe notes of 36 patients with idiopathic intracranial hypertension under regular review for at least 12 months by a single neuro-ophthalmologist were retrospectively reviewed. Weight was recorded at each assessment and weight loss recommended. Treatment was adjusted according to symptoms, visual function including visual fields and optic disc appearance only.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 13 publications
1
36
0
1
Order By: Relevance
“…An animal study found an association between increased intraabdominal pressure and an intracranial pressure elevation [8]. Intracranial hypertension as a consequence of raised intra-abdominal pressure may explain why weight reduction is associated with clinical improvement, improvement of papilledema and lowering of CSF pressure [27,40,44]. Sugerman and co-workers [41] found a high rate of treatment success after surgical (bariatric) treatment of obesity.…”
Section: Discussionmentioning
confidence: 96%
“…An animal study found an association between increased intraabdominal pressure and an intracranial pressure elevation [8]. Intracranial hypertension as a consequence of raised intra-abdominal pressure may explain why weight reduction is associated with clinical improvement, improvement of papilledema and lowering of CSF pressure [27,40,44]. Sugerman and co-workers [41] found a high rate of treatment success after surgical (bariatric) treatment of obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence from clinical studies indicates that papilledema is more rapidly reversed or more easily controlled if weight-loss is achieved [4][5][6][7][8][9][10]. However, previous studies evaluated weight-loss in relation to resolution of papilledema, not in relation to CSF-pressure.…”
Section: Discussionmentioning
confidence: 98%
“…Studies suggest that papilledema can be more readily controlled if weight-loss is achieved, but the association between weight loss and ICP reduction has not been established [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…IIH is closely associated with obesity, and weight reduction has been shown to improve the rate of recovery and prognosis in overweight patients [18,26,35,41,44]. At baseline patients entered a course of dietary recommendations and follow-up visits resulting in an overall initial weight loss [37].…”
Section: Discussionmentioning
confidence: 99%